Journey to Gonzales - Cuate, Melodie A. (Lubbock, Tex. : Texas Tech University Press, 2008)
When Mr. Barrington's trunk transports Nick, Hannah, and Jackie to Gonzales, Texas, in 1835, the girls end up in a military camp and learn about life in the Mexican army, while Nick participates in events leading up to the Battle of Gonzales.
Keywords: Time travel -- Juvenile fiction; Schools -- Juvenile fiction; Time travel -- Fiction; Schools -- Fiction; Gonzales, Battle of, Gonzales, Tex., 1835 -- Juvenile fiction; Texas -- Juvenile fiction. -- History -- Revolution, 1835-1836; Gonzales, Battle of, Gonzales, Tex., 1835 -- Fiction; Texas -- Fiction. -- History -- Revolution, 1835-1836; Fiction